Comparison of Myocardial Perfusion Scintigraphy Before and After Coronary Bypass Surger - Malik, Asad; Hussain, Fida; Tariq, Aleena; Adil, Muhammad; Hussain, Mehmood; Sikandar, Zeeshan (Pakistan Armed Forces Medical Journal, 2025)
Objective: To study the change in left ventricular perfusion as well as functional parameters before and after Coronary Artery Bypass Grafting (CABG) using myocardial perfusion scintigraphy. Study Design: Prospective observational study. Place and Duration of Study: Nuclear Medical Centre, Armed Forces Institute of Pathology, Rawalpindi, from Feb 2019 to Jan 2022. Methodology: A total of 42 patients, scheduled for CABG, underwent myocardial perfusion scintigraphy (MPS) using 99mTc-sestamibi, before and 8-12 weeks after surgery. Pre and post operatively, left ventricular relative perfusion and functional parameters were analyzed using commercially available software by two independent nuclear physicians. Results: Among the enrolled patients (n=42), 38(90.5%) were male while 4(9.5%) were female with mean age of 61.04±8.82 years. Left ventricular ejection fraction improved and was found to be statistically significant (38.93±8.19 to 46.26±10.46, p-value <0.01). Similarly, wall motion increased significantly in anterior and lateral segments with concomitant decrease in septal wall motion. A correlation was observed post-operatively between change in ejection fraction and wall motion (r=0.76) while significantly improved post-CABG radiotracer uptake was seen in almost all myocardial segments which showed reversible ischemia with resting perfusion ≥50% in 97 segments with fixed perfusion defects on pre-CABG resting perfusion, but ≤50% did not show any significant improvement, while 5 segments with pre-CABG resting perfusion ≤50% showed improvement on post-CABG MPS. Conclusion: There is significant improvement in left ventricular perfusion and functional parameters after CABG as assessed by myocardial perfusion scintigraphy.